Disaster Management Governance From A Public Administration Perspective: Evidence From Deli Serdang Regency, North Sumatra, Indonesia - Ade Wahyuni Azhar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines disaster management governance in Deli Serdang Regency, North Sumatra, from a public administration perspective, emphasizing disaster governance as an administratively embedded and multi-dimensional process rather than a purely technical function. Using a qualitative descriptive case study design, the research analyzes how institutional arrangements, administrative capacity, inter-agency coordination, community participation, and accountability interact in shaping local disaster management practices, with particular attention to the 2025 flood events. Data were collected through document analysis, secondary data review, and targeted literature analysis, and were examined using thematic analysis guided by public administration and collaborative governance theories. The findings indicate that while formal disaster management institutions and policies are in place, governance practices remain largely reactive, with limited emphasis on preparedness, mitigation, and long-term risk reduction. Administrative capacity constraints, fragmented coordination, under-institutionalized collaboration, and minimal community involvement in planning processes significantly restrict governance effectiveness